Unveiling the common loci for six body measurement traits in Chinese Wenshan cattle - Ren, Honghui; He, Xiaoming; Lu, Ying; Yue, Dan; Liu, Xingneng; Wu, Dongwang; Zhu, Junhong; Gao, Zhendong; Xi, Dongmei; Deng, Weidong (Frontiers in Genetics, 2023)
Body measurement traits are integral in cattle production, serving as pivotal criteria for breeding selection. Wenshan cattle, a local breed in China's Yunnan province, exhibit remarkable genetic diversity. However, the molecular mechanisms regulating body measurement traits in Wenshan cattle remain unexplored. In this study, we performed a genome-wide association method to identify genetic architecture for body height (BH), body length (BL), hip height (HH), back height (BAH), waist height (WH) and ischial tuberosity height (ITH), using the Bovine 50K SNP Array in 1060 Wenshan cattles. This analysis reveals 8 significant SNPs identified through the mixed linear model (MLM), with 6 SNPs are associated with multiple traits and 4 SNPs are associated with all 6 traits. Furthermore, we pinpoint 21 candidate genes located in proximity to or within these significant SNPs. Among them, Scarb1, AACS and HIVEP3 were implicated in bone formation and rarely encountered in livestock body measurement traits, emerge as potential candidate genes regulating body measurement traits in Wenshan cattle. This investigation provides valuable insights into the genetic mechanisms underpinning body measurement traits in this unique cattle breed, paving the way for further research in this domain.The nutritional value of beef, characterized by its high-quality animal protein content, underscores its significance in the meat market (Wu G, 2020). With an escalating demand for beef due to the increased consumption, understanding and enhancing the economic traits associated with beef cattle have become paramount (MacDonald, 2003). Body measurement traits, such as body length (BL), body height (BH) and back height (BAH), are widely used as important indicators for selection criterion to improve the production of the beef cattle (Gritsenko et al., 2023). According to previous study, these